Study guides

☆☆

Q: -14 -6 plus 4y

Write your answer...

Submit

Still have questions?

Related questions

so = -4y < -20 making y < 5

4y+6+9=4y+15

4y+2 = 2y+6 4y-2y = 6-2 2y = 4 y = 2

6-2x-8+3+12x+4y 10x+4y+1 Note that - -3 = +3 and that - -4y = +4y

5y + 6

This simplifies to 3x-6+4y.

If: -4y+7 = 35-6 then y = -5.5

(4y + 1)(y + 6)

6+(-2x-8)-(-3+12x)-(4y)= 6-2x-8+3-12x-4y=1-14x-4y 1-14x=4y (1-14x)/4=y

2 - 8y + 6 = 4y - 702 + 6 + 70 = 4y + 8y78 = 12yy = 78/12y = 6.5

First rearrange these simultaneous equations in the form of: 7x-4y = 26 5x-4y = 14 Subtract the bottom equation from the top equation remembering that a - - is equal to a plus. So, -4y - - 4y = 0 2x = 12 and therefore it follows that x = 6 Substitute the value of x into the original equations to find the value of y: Therefore: x = 6 and y = 4

y=2

People also asked